Investigating the effects of hospital privatization on performance and quality of care - Oliver Tiemann; Jonas Schreyögg (Verein für Socialpolitik, 2010)
In this paper, we investigated the post-acquisition effects of privatization on hospital performance in Germany. Our findings show that there was a significant positive impact of privatization on hospital performance. Private for-profit privatizations, in particular, outperformed hospitals privatized by private non-profit organizations, both in terms of efficiency and quality-adjusted efficiency. These key findings remained unchanged after conducting a number of sensitivity checks. Taking the effect of the introduction of DRG payments in 2003 into account it is striking that the efficiency gains of privatized hospitals were significantly larger in the post-DRG era. Moreover, privatized hospitals operating in regions with less competition realize significantly larger efficiency improvements.
Keywords: I10; L20; L30; 330